Effect of Zinc Sulfate on Wound Healing. An Experimental Study - Malti Gupta; S. K. Khanna; T. C. Jain; P. Prasad; N. K. Jha (Indian Journal of Plastic Surgery)
(1) The dog, an easily available and cheap animal, has been utilised for conducting experiments on wound healing. Methods to prevent licking of the wound have been described.